A multi-technique investigation of the nanoporosity of cement paste - Constantinides, Georgios; Jennings, Hamlin M.; Thomas, Jeffrey J. (My University, 2007)
The nanometer-scale structure of cement paste, which is dominated by the colloidal-scale porosity within the C-S-H gel phase, has a controlling effect on concrete properties but is difficult to study due to its delicate structure and lack of long-range order. Here we present results from three experimental techniques that are particularly suited to analyzing disordered nanoporous materials: small-angle neutron scattering (SANS), weight and length changes during equilibrium drying, and nanoindentation. Particular attention is paid to differences between pastes of different ages and cured at different temperatures. The SANS and equilibrium drying results indicate that hydration of cement paste at 20 °C forms a low-density (LD) C-S-H gel structure with a range of gel pore sizes and a relatively low packing fraction of solid particles. This fine structure may persist indefinitely under saturated conditions. However, if the paste is dried or is cured at elevated temperatures (60 °C or greater) the structure collapses toward a denser (less porous) and more stable configuration with fewer large gel pores, resulting in a greater amount of capillary porosity. Nanoindentation measurements of pastes cured at different temperatures demonstrate in all cases the existence of two C-S-H structures with different characteristic values of the indentation modulus. The average value of the modulus of the LD C-S-H is the same for all pastes tested to date, and a micromechanical analysis indicates that this value corresponds to the denser and more stable configuration of LD C-S-H. The experimental results presented here are interpreted in terms of a previously proposed quantitative "colloid" model of C-S-H gel, resulting in an improved understanding of the microstructural changes associated with drying and heat curing.
Keywords: Calcium; Silicates; Temperature; Hydrates; Nanostructured materials